A case‐study of policy change in residential service provision for adult persons with intellectual disability in Ireland. (25th June 2019) - Kelly, Caraíosa; McConkey, Roy; Craig, Sarah
Abstract: In Europe, many people with intellectual disabilities continue to live in congregated settings. In 2012, Ireland formally introduced a resettlement policy with people moving to live in more personalised arrangements. This longitudinal country case‐study aimed to monitor the implementation of this policy and the intra‐country variations that arose using the records maintained in the National Intellectual Disability Database. Details of over 4, 000 people living in congregated settings were examined in 2007 and again in 2012 and 2017. In addition, people who moved from such settings from 2007 onwards were tracked and the number of new admissions to them was estimated over the 10‐year period. Overall there was nearly a 30% drop in the numbers of people in congregated settings but the reductions varied markedly across the country and by 2017 the disparity was greater than in 2007. Also by 2017 persons aged over 55 years were eight times more likely to be accommodated in congregated settings. The case‐study illustrates the value of a longitudinal dataset for monitoring policy implementation across a diversity of provider organisations and administrative areas.